Determinación del estado epidemiológico de piroplasmosis y anaplasmosis bovina en el cantón El Pangui, provincia de Zamora Chinchipe - Narváez Jima, Jenny Margarita (2020)
Bovine piroplasmosis and anaplasmosis are re-emerging infectious diseases, cau- sed by Babesia bovis or Babesia bigemina and Anaplasma marginale, respectively. They are endemic in many countries of the world that have a tropical or subtropi- cal climate and the presence of ticks (vectors). The objective of this study was to determine the epidemiological status of bovine piroplasmosis and anaplasmosis in the El Pangui canton (Zamora Chinchipe province), through the study of 241 bovine females. A two-stage sampling was used: the farms were randomly selected and on the other hand, the bovine females older than two years of age (without condition of race, origin, or presence of ticks); 241 animals were sampled in 67 farms. From each of the animals, a blood sample was taken from the coccygeal vein in a tube with anticoagulant, these samples were analyzed by microscopic observation after perfor- ming the Giemsa staining technique. 44.81 % were positive samples for Babesia spp, while 73.03 % positive samples for Anaplasma spp 38.59 % of the animals presented co-infections with both agents. Provenance was a factor associated with the presen- ce of Babesia spp and Anaplasma spp (p<0,05), decreasing the risk in El Pangui parish vs. El Guismi parish; likewise, age was a factor associated with babesiosis (p≤0.05), since the risk increases in animals over 5 years of age vs. younger animals. In conclusion, it was possible to determine a high prevalence of piroplasmosis and anaplasmosis in bovine females from the El Pangui canton in the province of Zamora Chinchipe, confirming that the study area is an endemic region for babesiosis and bo- vine anaplasmosis, due to the presence of vectors, where animals generally develop coinfectious immunity and remain healthy carriers. Key words: Babesia spp, Anaplasma spp, Giemsa, tropical, vectors.